Potential of Malaysian seaweed extracts in inhibiting Ganoderma boninense and identification of their antifungal compounds - Abdul Aziz, Syamimi Diyana (2018)
Basal stem rot (BSR) disease is the most devastating disease in oil palm (Elaies guineensis) caused by a fungal pathogen, Ganoderma boninense. Various control measures have been tested but to date the utilization of seaweeds as a source of control agent has not been explored. This study investigated the antifungal potential of Malaysian seaweed extracts against G. boninense and identifying the potential antifungal compounds. Polar and non- polar compounds were extracted from cfSargassum oligocystum, Caulerpa racemosa, Caulerpa racemosa var. lamourouxii and cfHalimeda macrophysa using water, methanol, chloroform, dichloromethane and hexane. Methanolic extracts from all species displayed the highest yield with an average of 15.25 % compared to dry weight. At 0.25 mg/mL, C. racemosa var. lamourouxii dichloromethane extract recorded the highest growth reduction against G. boninense with 46.82 % followed by C. racemosa var. lamourouxii hexane extract with 36.43 % and cfH. macrophysa dichloromethane extract with 33.49 %. Statistical analysis from Kruskal-Wallis H test showed significant difference (H=77.23, p=.00) in growth reduction percentage between the different solvent. Dominant compounds detected via Gas Chromatography-Mass Spectrometry in extracts with antifungal potential were l-(+)-ascorbic acid 2,6-dihexadecanoate, phytol, tetradecanoic acid, isobutyl methylphosphonofluoridate and benzenamine,2-[2-(4-pyridinyl) ethyl]-. Further antifungal testing using standard phytol showed growth inhibition of G. boninense with 21 % inhibition and the amount of phytol in dichloromethane extracts were quantified via GC-MS. Dichloromethane extract of C. racemosa var. lamourouxii, cfH. macrophysa, C. racemosa and cfS. oligocystum contain 474, 117, 106 and 19 mg/L of phytol, respectively which were consistent with exhibited antifungal activities. These findings suggested that Malaysian seaweeds have potential as a source of natural and potent antifungal compounds for utilization in controlling the oil palm disease in Malaysia.